Hubungan antara Burnout Belajar dengan Perilaku Displacement pada Mahasiswa Bimbingan dan Konseling FKIP Universitas Nusa Cendana - Noviatri, Elisabeth Agnesia; Lohmay, Imanuel; Korohama, Katharina E.P.; Apriliana, I Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to determine: (1) a description of learning burnout, (2) a description of displacement behavior, (3) the relationship between learning burnout and displacement behavior in BK FKIP Undana students. This research uses a quantitative approach. The population is students, amounting to 483 students. The sampling technique used proportional stratified random sampling so that a sample of 80 students. The data collection technique is a questionnaire. Data analysis, namely descriptive and correlation analysis techniques with the help of the SPSS version 26 program. The results of this study include: (1) a picture of burnout learning for BK FKIP Undana students, very high category of 1 student (1.25%), high category of 43 people students (53.75%), low category as many as 33 students (41.25%), very low category as many as 3 students (3.75%). (2) description of displacement behavior in BK FKIP Undana students, very high category of 1 student (1.25%), high category of 54 students (67.5%), low category of 25 students (31.25%) ), very low category of 0 students (0%). (3) there is a relationship between learning burnout and displacement behavior in BK FKIP Undana students, where r value is 0.404 > r table with a significance of 0.05 = 0.219.